Are You and Your Significant Other Compatible? - Gabriella Foe (Voices in Bioethics, 2014)
Compatibility is of great importance when it comes to relationships. After all, every match-making website asks many questions, from personality types to habits to pet peeves, in order to determine whether or not two people will be a good match. But there is another type of compatibility criteria that is becoming increasingly important: your genetic material. ThePerfect46 is a genetics company that claims to determine whether you are with “the one,” according to your genes. They focus on ensuring that your offspring will be free from known genetically heritable diseases.